Level of Understanding of Students At SMP Negeri 22 Bengkulu City Regarding Online Gender-Based Violence - Larasti, Nuraini; Nopianti, Heni; Widiyarti, Diyas (Pascasarjana IAIN Metro, 2025)
The rapid development of social media brings new challenges for adolescents, one of which is an increased possibility of online gender-based violence. An adequate understanding of the definition, types, and effects of online gender-based violence is needed because adolescents, especially junior high school students, are a vulnerable group. Chi-square test analysis is a descriptive quantitative method used in this study. Data were collected through questionnaires distributed to 60 eighth-grade students at SMP Negeri 22 Bengkulu city. Symbolic interaction theory was used in this study to understand how students perceive online gender-based violence based on their experiences and social interactions. The results showed that students' understanding of online gender-based violence was good, with an average score of 4.00. Most students understood the definition, forms, and impacts of online gender-based violence and were aware that victims of online gender-based violence could come from various genders and ages. Students' knowledge was obtained through social media, education at school, and socialization from related institutions. This study emphasizes the importance of strengthening sustainable gender-based digital education in schools to increase awareness and prevent online gender-based violence among adolescents